Isolement, Identification Et Activite Antifongique De Deux Sesquiterpenes D’asteriscus Graveolens Subsp. Odorus (Schousb.) Greuter - Hakim Alilou; Bouchaib Bencharki; Mohammed Akssira; Lalla Mina Idrissi Hassani; Noureddine Barka (European Scientific Journal, ESJ, 2016)
Two sesquiterpenes of Asteriscus graveolens subsp. odorus, have been extracted, separated, purified and identified by NMR and IR: the naupliolide and asteriscunolide 3c. The valuation of these compounds is part of the search for a preventive approach of integrated control to reduce significantly the use of pesticides and especially the fungicide ones. The results revealed a strong inhibitory effect on naupliolide against Botrytis cinerea, Penicillium digitatum and Penicillium expansum dice concentration of 200 ppm. The asteriscunolide 3c showed a remarkable effect against Botrytis cinerea from the concentration of 150 ppm.